2018
DOI: 10.3390/f9080488
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Natural and Artificial Weathering on the Colour Change of Different Wood and Wood-Based Materials

Abstract: The importance of the aesthetic performance of wood is increasing and the colour is one of the most important parameters of aesthetics, hence the colour stability of twelve different wood-based materials was evaluated by several in-service and laboratory tests. The wood used for wooden façades and decking belongs to a group of severely exposed surfaces. Discolouration of wood in such applications is a long-known phenomenon, which is a result of different biotic and abiotic causes. The ongoing in-service trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…The objective of this model house was to comprehensively assess the technical and aesthetic service life of wood. The aesthetic service life has been reported already [23], so this manuscript focusses on the technical service life only. The average temperature in Ljubljana is 10.4 • C, the annual precipitation is 1290 mm and the Scheffer Climate Index is 55.3.…”
Section: Methodsmentioning
confidence: 99%
“…The objective of this model house was to comprehensively assess the technical and aesthetic service life of wood. The aesthetic service life has been reported already [23], so this manuscript focusses on the technical service life only. The average temperature in Ljubljana is 10.4 • C, the annual precipitation is 1290 mm and the Scheffer Climate Index is 55.3.…”
Section: Methodsmentioning
confidence: 99%
“…Weathering causes loss of gloss and colour and leads to cracks and change in chemical composition, erosion and roughening of wood surfaces [1,2]. Due to this fact, the appearance of wood changes over the course of several months, with bacteria, moulds and wood-colouring fungi [3,4] contributing to the overall change in colour. Natural weathering can be partially reproduced via artificially accelerated weathering in UV chambers equipped with water spray.…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal influence on the number of colonies within the first four millimeters of the samples was less clear. Kržišnik et al reported seasonal variation in color changes of uncoated wood for samples exposed outdoors in Slovenia for four years [20]. According to the authors, the most important reason for seasonal fluctuations was related to fungal melanin, with its formation on one hand being countered by bleaching on the other.…”
Section: Discussionmentioning
confidence: 99%